Expert group opinion for diagnosis and management viral hepatitis in solid organ transplant recipients in South Asia - Neeraj Saraf; Swapnil Dhampalwar; Vivek Kute; Shyam Bihari Bansal (Indian Journal of Transplantation, 2022)
Viral hepatitis is endemic in the South Asia region and is mainly caused by four hepatotropic viruses: hepatitis A virus (HAV), hepatitis B virus (HBV), hepatitis C virus (HCV), and hepatitis E virus (HEV). South Asia region consists of developing countries and HAV and HEV infections are common because of poor sanitary conditions and hygiene practices. HAV and HEV are transmitted person-to-person by fecal‒oral route. HBV and HCV are transmitted via permucosal or percutaneous exposure. It is important to know the impact of these viral infections in the setting of transplantation including evaluation and management in pre, peri, and posttransplant periods. This review summarizes the epidemiology, preventive practices, and advisory for travelers to these endemic regions. Furthermore, recommendations for screening donors and recipients in transplant settings are discussed.